The Cathedral Performance as a Prestigious Model: The Iconographical Program of the Mare de Déu i els Profetes Altar-Frontal - Beltrán González, Martí (Eikón / Imago, 2012)
The aim of this article is the study of the iconographical program of the Sant Vicenç d’Espinelves altar-frontal (Osona), possibly made in a panel painting workshop related to the Vic cathedral, whose liturgy and paraliturgy in the second half of the 12th century was clearly the source of their different scenes. In order to outline the liturgical background of the conception of this iconographical program, our analysis is focused in the study of both the liturgy and the space where these ceremonies took place.